2005
DOI: 10.1016/j.eupc.2005.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Indication of the radiofrequency induced lesion size by pre-ablation measurements

Abstract: Pre-ablation measurement of DeltaIMP and DeltaT can indicate the lesion size resulting after ablation in temperature-controlled, power-controlled and irrigated ablation in vitro, since DeltaT reflects cavitary cooling and to a smaller extent electrode-tissue contact, and DeltaIMP reflects only electrode-tissue contact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…However, all of them are dependent, to a certain degree, on real contact between catheter and tissue. 16,17,25,26 Two recently published studies, the Toccata 28 and the EFFICAS I 29 trials, confirmed the relevance of applied contact force during AF ablation in terms of recurrences of the arrhythmia 28 or of the incidence of gaps in PV isolation. 29 Our study shows that, during manual and robotic advancement of the catheter, the force applied at ablation level is likely to be 420 g, which identifies a threshold with high likelihood of transmurality 26 and low recurrences at follow-up, 28 but still within a safety limit for the occurrence of pops 16,30 and thrombi.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…However, all of them are dependent, to a certain degree, on real contact between catheter and tissue. 16,17,25,26 Two recently published studies, the Toccata 28 and the EFFICAS I 29 trials, confirmed the relevance of applied contact force during AF ablation in terms of recurrences of the arrhythmia 28 or of the incidence of gaps in PV isolation. 29 Our study shows that, during manual and robotic advancement of the catheter, the force applied at ablation level is likely to be 420 g, which identifies a threshold with high likelihood of transmurality 26 and low recurrences at follow-up, 28 but still within a safety limit for the occurrence of pops 16,30 and thrombi.…”
Section: Discussionmentioning
confidence: 57%
“…[15][16][17] Traditional indirect indicators of efficacious RF ablation are impedance increase pre-RF delivery, 25 drop in impedance 15,17,26 and increase in temperature with tissue heating, 15,16,25 and use of ICE to assess tissue contact. However, all of them are dependent, to a certain degree, on real contact between catheter and tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lesion size depends on tissue temperature which relates to controllable and noncontrollable factors. 1 Controllable factors include catheter tip size (tip surface area), tip orientation, power settings, application time, and temperature cut-off. Non-controllable factors include tip cooling by blood flow and tissue contact.…”
mentioning
confidence: 99%
“…These factors have been studied extensively. [1][2][3][4][5][6] A magnetic navigation system (Niobe, Stereotaxis Inc., St. Louis, MO, USA) allows the use of floppy magnetic tip catheters, steered and advanced remotely, using an applied magnetic field and an external advancer system. These catheters may have advantages in positioning in difficult anatomy, and also in maintaining position during ablation.…”
mentioning
confidence: 99%